ANALISIS EFISIENSI INDUSTRI RUMAH TANGGA EMPING MELINJO DENGAN METODE DEA (Data Envelopment Analysis) DI KABUPATEN KLATEN - Heppy Susilowati; Slamet Hartono (Fakultas Pertanian UST, 2018)
The purpose of this research is to knowing the cost of production, income, profit, BEP condition, efficiency level based on DEA (Data Envelopment Analysis) method and improvement step in emping melinjo of home industry in Klaten Regency. The basic method of research used is analytical descriptive method. Determination of sample area that used by researcher is purposive method . The results showed that the average monthly production cost (December 2016) was Rp 3,496,782.24. The cost of production in the melinjo chips domestic industry in Klaten Regency is divided into two, namely explicit and implicit costs. The average total revenue received by the emping melinjo producer is Rp 4,196,667.67 per month, the average monthly income is Rp 1,533,792.45 and the average profit earned during the month is Rp 694,886.23. Production volume at BEP conditions based on total cost is 15.96 kilograms and 0.88 kilograms based on explicit cost. The result of efficiency level analysis with DEA method shows the average efficiency level of producer is 0.77. Of the 30 respondents there are only 5 manufacturers whose business is efficient. Improvement steps to improve efficiency is to adjust between the actual value of input and output with the target value of the DEA analysis results.From the result of research, it is concluded that efficiency level of home industry of emping melinjo in Klaten Regency is still low. The proposed suggest that producers can use input variables as optimally as possible and maximize output to achieve the efficiency.